The The Effect of Capital Structure on Profitability and Stock Returns In Banks Listed on The Indonesia Stock Exchange, 2021-2025 - Januar Afrino; Listiana Sri Mulatsih; Sefrimel Angriani Zn3 (Jurnal Manajemen Universitas Bung Hatta, 2026)
This study examines the effect of capital structure on profitability and stock returns among banking companies listed on the Indonesia Stock Exchange during the 2021-2025 period. Capital structure is proxied by the Debt-to-Equity Ratio (DER), profitability is proxied by Return on Equity (ROE), and stock returns are measured using annual stock returns. The study applies an explanatory quantitative approach using balanced panel data from 12 banks over five years, yielding 60 bank-year observations. The model is estimated without control variables in order to remain consistent with the conceptual framework, which positions DER as the independent variable, ROE as the profitability variable, and stock returns as the market-based dependent variable. The estimation results show that DER has a significant negative effect on ROE, DER has a significant negative effect on stock returns, and ROE has a significant positive effect on stock returns. These findings indicate that a bank's capital structure is not only associated with shareholder profitability but also with the market's response to banking stocks.